2014
DOI: 10.1016/j.devcel.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A Switch from Low to High Shh Activity Regulates Establishment of Limb Progenitors and Signaling Centers

Abstract: The patterning and growth of the embryonic vertebrate limb is dependent on Sonic hedgehog (Shh), a morphogen that regulates the activity of Gli transcription factors. However, Shh expression is not observed during the first 12 hr of limb development. During this phase, the limb bud is prepatterned into anterior and posterior regions through the antagonistic actions of transcription factors Gli3 and Hand2. We demonstrate that precocious activation of Shh signaling during this early phase interferes with the Gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
79
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(93 citation statements)
references
References 34 publications
(66 reference statements)
12
79
2
Order By: Relevance
“…In particular, simultaneous inactivation of Irx3/5 and Gli3 caused failure to establish a Shh-expressing ZPA, and caused trace Fgf8 expression in the AER. However, this phenotype was hindlimb specific and forelimbs developed polydactyly, similar to Gli3 KO limbs (11). In significant contrast to this report, we found that Sall4-Gli3 cooperation regulates limb signaling center development in both fore-and hindlimbs.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In particular, simultaneous inactivation of Irx3/5 and Gli3 caused failure to establish a Shh-expressing ZPA, and caused trace Fgf8 expression in the AER. However, this phenotype was hindlimb specific and forelimbs developed polydactyly, similar to Gli3 KO limbs (11). In significant contrast to this report, we found that Sall4-Gli3 cooperation regulates limb signaling center development in both fore-and hindlimbs.…”
Section: Discussioncontrasting
confidence: 56%
“…Gli3 functions for specifying anterior-posterior polarity in the nascent limb buds (9), and Gli3 null embryos develop polydactyly without polarity (10). Furthermore, simultaneous inactivation of Gli3 and Irx3/5 caused failure to express Shh and significantly reduced levels of Fgf8, which resulted in severe limb truncation (11). This result suggests that cooperation of anterior genes is upstream of establishing limb signaling centers, and therefore expansion of SHH-dependent posterior progenitors.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…3G, H, J, K). These phenotypes were consistent with compromised Gli3 REP function [3133]. To determine whether digit defects in Sufu T396I/T396I are due to impaired Gli3 REP activity, we forced expression of a constitutive Gli3 REP allele ( Gli3 ∆699 ), which produces a truncated protein due to a premature termination codon [34], in the Sufu T396I/T396I background.…”
Section: Resultsmentioning
confidence: 99%
“…Sufu knock-out mice display early embryonic lethality at E9.5, with severe cranio-facial and neural closure defects related to constitutive SHH pathway activation, 31 similar to that observed in Ptch1 mutants. 32 Limb-specific conditional deletion of Sufu results in polydactyly due to a block in Gli3R processing, 33,34 whereas mouse embryos with conditional knock-out of Sufu in the mid-hindbrain show altered morphology of the brainstem and cerebellum and delayed differentiation and abnormal migration of most cerebellar cell types. 35 Here, we show that germline hypomorphic variants of SUFU cause deregulation of the SHH pathway, resulting in recessive stereotypical developmental defects of the CNS and limbs which share peculiar features with both SHH-related disorders and with ciliopathies such as JS.…”
Section: Introductionmentioning
confidence: 99%